Synthesis, characterization and cytotoxicity of polyethylene glycol coupled zinc oxide–chemically converted graphene nanocomposite on human OAW42 ovarian cancer cells. (28th September 2015) - Naskar, Atanu; Bera, Susanta; Bhattacharya, Rahul; Roy, Sib Sankar; Jana, Sunirmal
Abstract : Present work reports for the first time on successful synthesis of polyethylene glycol (PEG) coupled ZnO–chemically converted graphene (CCG) nanocomposites (ZGP) as well as pristine nano ZnO (ZO), ZnO–CCG (ZG) and ZnO–PEG (ZP) by adopting facile solvothermal method using zinc acetate dihydrate, graphene oxide and PEG as precursor materials. X‐ray diffraction measurement of samples showed nanocrystalline hexagonal ZnO. Agglomeration of ZnO nanoparticles formed microspheres in ZG, and the agglomeration was found to be decreased in ZGP as revealed from field emission scanning and transmission electron microscopes. Raman and FTIR spectral studies evidenced the presence of chemically interacted CCG and polyethylene glycol in the nanocomposites. Content of the organics in ZGP was determined by thermogravimetric analysis. A mechanism was proposed on the formation of ZGP nanocomposite. From the measurement of in vitro cytotoxicity, quantitative cell viability (CV) of human ovarian cancer cell line, OAW42, was obtained from control to a maximum of 200 µg/ml of sample concentrations. An excellent CV of the cancer cells was observed (nearly ~80% of viable cells at 50 µg/ml dose with respect to the control) for ZGP compared to ZO, ZG and ZP samples. The effective role of CCG and PEG in ZGP nanocomposite for enhancing the cell viability was explained. This simple strategy could be beneficial for synthesis of other metal oxide towards biomedical applications. Copyright © 2015 John Wiley & Sons, Ltd.